Construction of a plant transformation vector containing a partial isochorismate syhthase cDNA - Tai, Ker Shing (Universiti Malaysia Sarawak (UNIMAS), 2012)
Isochorismate synthase (ICS) is an enzyme that catalyzes chorismate into isochorismate. Isochorismate is a channel for the production of secondary metabolites such as anthraquinone and phylloquinones. A 1502 bp fragment partial ICS cDNA was amplified from pGEM-T vector through PCR using a set of primers. A binary vector, pGSA 1l31, was isolated from E. coli XLI Blue cells and was linearized using BamH 1 restriction endonuclease at the BamH 1 restriction site. Both cDNA and pGSA 1131 plasmid were subjected to end-blunting procedure. The partial ICS cDNA was ligated into pGSA 1131 binary vector through blunt end ligation to form a recombinant vector. Ligation mixture was transformed into competent E. coli XLI Blue cells via heat shock method. Single colonies were grown from a LB agar plate and five colonies were chosen and were heat disrupted to release their plasmid content. Colony PCR technique was performed using primers designed from conserved ICS domain. An amplified 800 bp fragment of the internal confirms the presence of the partial ICS cDNA in the colonies.